Humor, Persuasion, and Politics: The Impact of Memes on X during the 2024 U.S. Presidential Election Campaign - Trelles-Villanueva, Alicia; Carrasco-Polaino, Rafael; Sánchez de la Nieta, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Memes have become a significant aspect of political communication on social media. These elements serve as a creative and humorous means to express opinions and participate in political discourse. The persuasive power of political memes lies in their ability to frame issues and incorporate rhetorical elements that can influence their virality and impact on social media audiences. This study analyzes the engagement and sentiments conveyed by various memes published on the social network X during the 2024 U.S. presidential election campaign.